Dark prospects in Philippines' war on terror. - Francisco N. Cruz Jr. (2008)
The Sipadan crisis was the single most important event in the history of Islamic terrorism in the Philippines. Perpetrated by the Abu Sayyaf Group (ASG), which dreams of converting Mindanao into an Islamic state, it marked the internationalization of the Islamist cause and the transnational character of ASG brand of terror.